2002
DOI: 10.1007/s00223-002-1022-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alendronate on Periprosthetic Bone Loss After Total Knee Arthroplasty: A One-Year, Randomized, Controlled Trial of 19 Patients

Abstract: Undesired bone loss around implants is considered to occur mainly because of a stress-shielding phenomenon. Bone surrounding the total knee arthroplasty (TKA) adjusts its mineral density and structure to meet new mechanical demands. Immobilization, in combination with local operative trauma to the bone and soft tissues, has an additional impact on bone loss. The clinical survival of TKA is associated with the quality and quantity of the surrounding bone environment. Poor bone quality and quantity may predispos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 0 publications
1
41
0
3
Order By: Relevance
“…Oral alendronate was used in nine trials [11,13,14,19,[29][30][31][32][33], oral etidronate in two trials [9,15], oral risedronate in one trial [34], intravenous pamidronate in one trial [12], and intramuscular clodronate in one trial [10]. The dose and the duration of BP administration differed among the trials.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Oral alendronate was used in nine trials [11,13,14,19,[29][30][31][32][33], oral etidronate in two trials [9,15], oral risedronate in one trial [34], intravenous pamidronate in one trial [12], and intramuscular clodronate in one trial [10]. The dose and the duration of BP administration differed among the trials.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Several studies have investigated the use of bisphosphonates as adjuvant in implant fixation. [5][6][7][8][9][10] The general findings were increased peri-implant bone density or reduced implant migration.…”
Section: Introductionmentioning
confidence: 99%
“…Both bisphosphonates and parathyroid hormone (PTH) treatment have been reported to improve implant fixation, allowing for more durable joint replacements [22][23][24][25][26][27][28][29][30][31][32]. Indeed, in a recent study, we showed that both PTH and pamidronate were able to prevent the deleterious effects of an isocaloric protein restricted diet on bone microarchitecture close to the implant and on mechanical fixation in adult female rats [33].…”
Section: Introductionmentioning
confidence: 99%